IMPLEMENTASI APLIKASI FEEDER DIHUBUNGKAN DENGAN PERLINDUNGAN DATA PRIBADI DOSEN DAN MAHASISWA DITINJAU DARI UNDANG-UNDANG NOMOR 12 TAHUN 2012 TENTANG PENDIDIKAN TINGGI - Cunha, Theresia E. B. da; Tuba Helan, Yohanes G.; Tadeus, Dhey W. (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Technology is created to meet human needs. Advances in Information and Communication Technology (ICT) enforcing the implementation of Feeder applications benefits to education sector particularly to higher education. Feeder is a semester-based data reporting application for every higher educational institution in Indonesia, which is synchronized with the webpage of www.forlap.dikti.go.id. Feeder is a mandate of Article 56 Section 4 of ActNumber 12 Year 2012 Concerning Higher Education. As an information center application in college, Feeder encompass master data of everylecturer and student, learning process data, graduate data reporting and lecturer teaching activity. In the light of suchsubstance in Feeder in line with the fast progress of information technology.